(untitled) (Indian Journal of Pure & Applied Physics (IJPAP), 2024)
A series of lead-bismuth silicate glasses have been made via classical melt-quench route in the compositional range 20PbO∙(80-x)Bi2O3∙xSiO2 (where, x = 10, 20, 30, and 40mol%). Impedance spectroscopy was used to collect temperature-dependent conductivity data for the glass series in the range of frequency 10Hz-7MHz and at temperatures ranging from 473K-703K. The non-Debye type nature of relaxing ions is shown by complex impedance plots. From experimental impedance data, DC conductivity; σdc, power law exponent; s, activation energy for dc conduction; Edc, relaxation time; tMꞌꞌ, activation energy for relaxation; Eτ were extracted. The dc conductivity decreased with an increase in SiO2 content and was found to follow Arrhenius law. A close agreement in the values of activation energies determined from different formalisms suggested that during both the conduction and relaxation processes, the charge carriers must cross the similar height energy barrier.